Pembelajaran Profesionalisme Kedokteran dalam Persepsi Instruktur dan Mahasiswa - Cicih Bhakti Purnamasari; Mora Claramita; Yayi Suryo Prabandari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: Profesionalism has become a main competency for physician. Therefore, it is important to get an agreement from health provider about professionalism and it’s applicable learning method for medical institution. This research aimed to explore skills laboratory instructor and student’s perception of the learning method that can facilitate the mastery of professionalism and it’s professional behavior components.Method: A descriptive qualitative method was carried out in this research. Data was collected by indepth interview among instructors and FGD among two groups of students, and analyzed by grounded theory method approach.Results: Medical professionalism is an integrated ability of knowledge, skill and attitude. Professional behavior formed by attitude. Professionalism can be learnt and taught by eksplisit, implisit and continuing education methods.Conclusion :. Medical professionalism can be collaborated in several learning methods. Role model is claimed as an effective learning method for medical professionalism and professional behavior mastery.